Modernización de la gestión pública y la competencia laboral de los funcionarios de la Municipalidad Provincial de Ucayali 2022 - Flores Palomino, Gilberto (2023)
The purpose of this investigation was to determine the relationship between the modernization of public management and the labor competence of the officials of the Provincial Municipality of Ucayali. An applied approach was introduced and a descriptive-correlational design was used without experimentation. The target population consisted of 45 people to whom a survey was applied as a data collection method using a questionnaire as an instrument. The results obtained revealed that the modernization of public management was qualified as regular by 24% of those surveyed and as deficient by 22%. As for the dimension of open government, 24% misses it regularly and 22% describes it as deficient. Regarding the e-government dimension, 28% rated it regular and 20% deficient. In the dimension of institutional articulation, 22% miss it regularly and 22% as deficient. On the other hand, it was diminished that labor competencies are being developed on a regular basis. In conclusion, it will be prolonged that there is a significant and positive relationship between the modernization of public management and the labor competence of officials.